Pengaruh Leadership Style, Reward, dan Punishment terhadap Kinerja Karyawan pada PT. Hikmah Sejahtera Surabaya - Ariq, Arsalan Anjab; Prabowo, Budi (Universitas Batanghari, 2024)
PT Hikmah Sejahtera is a private company engaged in general trading. This research aims to determine how the influence of leadership style, reward, and punishment on the performance of employees of PT Hikmah Sejahtera Surabaya. The research method used in this research is a quantitative approach method with interviews, observation, documentation, and distributing questionnaires conducted by researchers in obtaining the required data. The population in this study were employees of PT Hikmah Sejahtera Surabaya, totaling 50 respondents. The analysis technique uses multiple linear regression analysis. Based on the results of this research it is concluded that the variable leadership style (X1), punishment (X3) can affect employee performance (Y) and reward (X2) has no effect on employee performance (Y). Of the three independent variables leadership style (X1), reward (X2), and punishment (X3) which have a dominant effect on the dependent variable employee performance (Y), the variable is punishment (X3) with a coefficient value of 0.327 which is the largest value among other variables.